Brønsted Acid Catalyzed Asymmetric SN2‐Type O‐Alkylations1. Issue 12 (10th February 2013) - Čorić, Ilija; Kim, Ji Hye; Vlaar, Tjøstil; Patil, Mahendra; Thiel, Walter; List, Benjamin
<x xml:space="preserve">Abstract</x> Bridging the gap: Brønsted acids catalyze an intramolecular SN2‐type alkylation of alcohols with ethers by bridging a pentacoordinate transition state, thus simultaneously activating both the leaving group and nucleophile (see scheme). Density functional calculations provide detailed insight into the course of the reaction and the transition‐state structure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>